Web Sales Based Information System Using A Cross-Selling Approach At Bebek Berkah Farm - Hibrizi, Muhammad Naufal Fathin; Suendri, Suendri (SEAN Institute, 2024)
Bebek Berkah Farm carries out sales management activities manually, including sales research via the web, without a support system. This research aims to create a website-based application. Design and build a website-based E-commerce application that contains a system to help companies handle the management of goods data, customer data, sales transactions, purchase transactions, inventory at Bebek Berkah Farm. The method used in this research is the SDLC waterfall model. The result of this research is that the sales application information system allows Bebek Berkah Farm to provide data from logging in to inputting payment information easily, orderly and easily accessible. This technology can also produce more detailed sales reports over a certain period of time. Bebek Berkah Farm can access the system so that customers can easily obtain information regarding sales at the Bebek Berkah farm. This can help companies to increase sales and provide a better shopping experience for customers. This system was built using web-based technology, so it can be accessed via a browser and is easy to use for both admins and customers. This system is expected to help Bebek Berkah Farm optimize sales of duck products and provide a better shopping experience for customers.